Strategic adjustment of parental care in tree swallows: life-history trade-offs and the role of glucocorticoids. Issue 12 (December 2016) - Akçay, Çağlar; Lendvai, Ádám Z.; Stanback, Mark; Haussmann, Mark; Moore, Ignacio T.; Bonier, Fran
Abstract : Life-history theory predicts that optimal strategies of parental investment will depend on ecological and social factors, such as current brood value and offspring need. Parental care strategies are also likely to be mediated in part by the hypothalamic–pituitary–adrenal axis and glucocorticoid hormones. Here, we present an experiment in tree swallows ( Tachycineta bicolor ), a biparental songbird with wide geographical distribution, asking whether parental care is strategically adjusted in response to signals of offspring need and brood value and if so, whether glucocorticoids are involved in these adjustments. Using an automated playback system, we carried out playbacks of nestling begging calls specifically to females in two populations differing in their brood value: a northern population in Ontario, Canada (relatively higher brood value) and a southern population in North Carolina, USA (relatively lower brood value). We quantified female offspring provisioning rates before and during playbacks and plasma corticosterone levels (cort) once during late incubation and once immediately after playbacks. Females in both populations increased feeding rates temporarily during the first 2 h of playback but the increase was not sustained for the entire duration of playback (6 h). Cort levels from samples at the end of the playback did not differ between control females and females that received playbacks. However, females that had higher increases in cort between the incubation and nestling period had greater fledging success. These results suggest that females are able to strategically respond to offspring need, although the role of glucocorticoids in this strategic adjustment remains unclear.